The PNAE (National School Feeding Program) activity system and its mediations - Alves Da Silva, Eliane; Pedrozo, Eugenio Avila; Nunes Da Silva, Tania (Frontiers in Environmental Science, 2023)
The National School Feeding Program (PNAE) is a Brazilian policy that aims to provide school meals to public school students. From Law No. 11,947, it was established that the minimum percentage of 30% was used to purchase foodstuffs directly from family farming. There are particularities to be observed; in addition to the general rules, it is possible to create specific rules for the operationalization of the program. Therefore, this paper aims to characterize the dynamic process of the relationships and actions of the social agents involved through the Activity System generated by Law No. 11,947 of 2009 in the municipality of Porto Velho in the state of Rondônia, located in the western Amazon. As a theoretical framework, Cultural Historical Activity Theory (CHAT) and Mediated Action Theory (MAT) were used. To achieve the objective, a qualitative research and abductive logic was used, using a unique and incorporated case study as a strategy. In all, 49 interviews were conducted and analyzed using content analysis. The extent of the influenced community and the different realities to which the actors are exposed were verified.